Android programming : the big nerd ranch guide - Phillips, Bill; Stewart, Chris;Hardy, Brian;Marsicano, Kristin (Atlanta, GA : Big Nerd Ranch, 2015)
Android programming : the big nerd ranch guide is an introductory android book for programmers with Java experience. Based on Big Nerd Ranch's popular android bootcamp, this guide will lead you through the wilderness using hand-on example apps combined eith clear explanations of key concepts and APIs. This book focuses on practical techniques for developing apps compatible with Android 4.1 (Jelly bean) through Andoird 5.1 (Lollipop) and beyond, including coverage of material design.
Learning Android The Necessary Tools 1. Your First Android Application 2. Android and Model-View-Controller 3. The Activity Lifecycle 4. Debugging Android Apps 5. Your Second Activity 6. Android SDK Versions and Compatibility 7. UI Fragments and the Fragment Manager 8. Displaying Lists with RecyclerView 9. Creating User Interfaces with Layouts and Widgets 10. Using Fragment Arguments 11. Using ViewPager 12. Dialogs 13. The Toolbar 14. SQLite Databases 15. Implicit Intents 16. Taking Pictures with Intents 17. Two-Pane Master-Detail Interfaces 18. Localization 19. Accessibility 20. Assets 21. Audio Playback with SoundPool 22. Styles and Themes 23. XML Drawables 24. More About Intents and Tasks 25. HTTP & Background Tasks 26. Loopers, Handlers, and HandlerThread 27. Search 28. Background Services 29. Broadcast Intents 30. Browsing the Web and WebView 31. Custom Views and Touch Events 32. Property Animation 33. Locations and Play Services 34. Maps 35. Material Design
Includes index.
Keywords: ANDROID (ELECTRONIC RESOURCE)